A review of gestational diabetes (GDM) management and outcomes based on the new international association of diabetes and pregnancy study groups (IADPSG) recommendations and booking BMI. (18th April 2012) - Tang, AW; Ballal, S; Goodfellow, L; Joseph, F; Davies, J
Abstract : Introduction: Obesity is an increasing problem. In October 2010, Countess of Chester Hospital adopted recommendations by IADPSG for diagnosis of GDM. We aimed to review the impact of the recommendations, and determine the association of booking BMI on glycaemic management and pregnancy outcomes. Methods: The number of GDM diagnosed 12 months before and after the change in criteria was compared. Data was retrospectively collected on women diagnosed with GDM using new criteria (fasting blood glucose ≥5.1mmol/l, 2 hr glucose ≥7.8mmol/l). Outcomes were compared between obese women (BMI≥30) and those with BMI<30. Results: In a mainly Caucasian population, 186 (15%) women were diagnosed with GDM (new criteria from 1228 OGTT), compared with 45 (4.1%) women diagnosed (old criteria from 1089 screened). Analysis of 82 cases (mean age 31±5.4, mean BMI 30±6.9kg/m2) diagnosed on the new criteria showed obese women had more adverse pregnancy outcomes and required more intervention with metformin (34.1% vs 23.7%) and insulin (29.5% vs 13.2%) for glycaemic control than non-obese women. Conclusions: The new recommendations have increased the diagnosis of GDM by 4 fold. Obesity may further increase the risks of perinatal morbidity associated with GDM, and the reasons for this needs further research.